TRADITIONAL ECOLOGICAL KNOWLEDGE AND VERTICAL FARMING PRACTICES IN SUSTAINABLE HIGHLAND AGRICULTURE: A CASE STUDY OF THE TENGGER COMMUNITY IN TOSARI VILLAGE, EAST JAVA - Agus Lintang Widodo; Ali Al Fagit; Lukmanul Hakim; Muhammad Arvangga Aditya; Nasrul Sidiq; Amani Salsabil Husodo (jses, 2025)
Agriculture is an attempt to establish an artificial ecosystem in charge of providing food for humans. The location of this research was conducted in Tosari Village, Tosari District, Pasuruan Regency. Tosari District is one of the areas located on the slopes of Mount Bromo. This research was conducted for 2 days, starting from October 29 to October 30, 2022. The data used in this study were primary and secondary data. The Tengger indigenous people who live in Tosari Village almost 90% depend on agricultural land for their lives. The geographical condition of the Tengger Tribe which is located in a mountainous area forces them to still be able to utilize the land into agricultural land using a profitable vertical cropping pattern (Larian). Potato is one of the main commodities produced by the local community. In addition, leeks, cabbage, carrots, corn and wheat are also plants that are often planted by the community